Causal beliefs of conversion disorder: a cross-sectional study - Latif, Sara; Aisha Sitwat (Journal of the Pakistan Medical Association, 2025)
Objective: To investigate causal beliefs pertaining to conversion disorder among clinical sample, caregivers and the general public. Method: The cross-sectional, quantitative, mixed-sample study was conducted from January to December 2023 after approval from ethics review board of the University of the Punjab, Lahore, Pakistan, and comprised patients diagnosed with conversion disorder in group A, their caregivers in group B, and members from the general community at large in group C. Data was collected using self-designed demographic information questionnaire and the Conversion Disorder Causal Belief Questionnaire. Data was analysed using SPSS 24. Results: Of the 300 subjects, 100(33.3%) were in group A with mean age 25.76+/-7.7 years, 100(33.3%) were in group B with mean age 43.22+/-11.4 years, and 100(33.3%) were in group C with mean age 32.42+/-12.02 years. Majority of the participants were females 215(72%), educated 276(92%) and working 281(94%). There were significant differences across all the groups in psychogenic, somatogenic, sociocultural, interpersonal and paranormal beliefs regarding conversion disorder. Group A had significantly higher levels of agreement on all domains (p<0.05) except for somatogenic myths compared to group B (p>0.05), and psychogenic facts compared to group C (p>0.05). Comparisons between groups B and C revealed significant differences in psychogenic facts, sociocultural facts and interpersonal myths (p<0.05). Conclusion: Causal beliefs about conversion disorder varied across clinical sample, their caregivers and the general public, where the clinical sample agreed more with both myths and facts about the cause of conversion disorder. Key Words: Conversion disorder, Causal beliefs, Aetiological factors.